ELECTION CALCULATIONS APPLICATIONS USING SMS PROGRAMMING DELPHI AND COMPONENT OXYGEN SMS - Rachmat Rachmat; Irfan, Skom., MMSI Irfan, Skom., MMSI (Jurnal Sistem Informasi, 2008)
The presence of an SMS-based technology in our lives is a big leap in the history ofthe human communication. SMS technology is the most modern communicationtechnology and the most promising both in terms of quality, efficiency and economy.The use of applications that are specific calculations that analyze a voice that comesinto the mobile media itself and accompanied by a caption- like specification resultdescription sounds into each prospective candidate, the writer tries to create an SMSapplication programming calculations using DELPHI and local elections OxygenSMScomponent.SMS application serves to make the process of counting of votes (vote). Applicationis two-way, meaning that incoming SMS will be rewarded by the system. From thisresearch we can conclude that by using computerized going more quickly andeffectively in the calculation of votes.